APLIKASI BASIS DATA RAWAT INAP PUSKESMAS PRAMBON - Nur Hidayati* Chatarina U** Windhu Purnomo*** (The Indonesian Journal of Health Science, 2016)
Inpatient database available in PHC Prambon still applies the conventionalway. This rises some problems for input, process and output activities. Therefore,on the recording and reporting of inpatient care, database on inpatientcare iscreated in order to obtain precise, fast, and valid data. The purpose of this databaseis to identify activities, the user needs toward recording and reporting on inpatientcareas well as creating and testing appropriate applications. This study applied aqualitative approach with action method research aiming to develop practicalknowledge in achieving the goal. This research was conducted at Prambon publichealth center with the object of research is inpatient recording and reporting aswell as informants and subjects fortesting the results. Identifying the user needs forthe database means finding an integrated registered patients with inpatients andalso with having theirID. Thus,the information obtained is accurate, fast and valid,with the output in the form ofdaily, monthlyrecapitulation report, BOR LOS, the tenhighest diseases, and data for preventing infectious diseases. Designing thedatabase application is conducted by first designing the user view, and a conceptualschema, namelydata normalizing, creating a data flow diagram, ERD, datadictionary, and designing the physical database. By using WEB-based applicationswith PHP and MySQL, the database was designed and created and then conductedwith the test to determine the barriers for health care workersin applying thedatabase application on inpatient care.